Expressing Reality through Spectacle and Dream in Baroque Art Karacsony, N.: Expressing Reality through Spectacle and Dream in Baroque Art - Karacsony, Noemi (Universitatea Transilvania Brasov, 2019)
Diversity and unity, dream and reality, the constant struggle between opposites – these are some of the ideas which mark the Baroque, as art period in the history of Western art, but as a perpetual concept as well. The present paper aims to reveal and explain the philosophical ideas which influenced the creation of Baroque artistic creations. The outer splendour is a mask which hides the deep torment of the artist, lavishness and opulence express the complexity of the human soul, torn between contradictions, a tension which can be perceived in Baroque music as well. The alto arias in the “Stabat Mater” of G. B. Pergolesi were chosen to explain, from a musical point of view, some of the philosophical concepts which define the Baroque.
Keywords: Baroque; mask; splendour; Pergolesi; “Stabat Mater”